Local and global in local communities - T. I. Makogon (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The author has carried out social and philosophic analysis of circumstances occurred in local communities under globalization and has determined the methods and forms of resistance to negative impact of global processes in local communities. New social phenomena caused by global impact are defined. The scale of globalizing processes and the level of interwinding of global and dependence relations in local communities in different interacting fields are matched up; the level of network inclusion into the field practices of the community is described. The local communities are represented as topological spaces having different spatial logics. The study allows perceiving the size of locality measured in scaling as a starting system along with national and global. Local communities are represented not only as global constructions but also as local constructions of the global. Globalization and localization are parallel processes in local communities.